Additive effect of brimonidine in maximum tolerated medical therapy for primary open-angle glaucoma - D.A. Dorofeev; V.P. Balukhtina; M.V. Es’kova; K.A. Efimova; E.V. Kirilik; K.O. Luk’yanova (РМЖ "Клиническая офтальмология")
D.A. Dorofeev1, V.P. Balukhtina2, M.V. Es’kova1, K.A. Efimova1, E.V. Kirilik1, K.O. Luk’yanova1 1City Clinical Hospital No. 2, Polyclinic № 1, Chelyabinsk, Russian Federation 2South Ural State Medical University, Chelyabinsk, Russian Federation Aim: to evaluate additive IOP-lowering effect of brimonidine 0.2% to achieve target IOP via enhancing maximum tolerated medical therapy for primary open-angle glaucoma (POAG). Patients and Methods: 63 patients (63 eyes) with advanced POAG and poorly controlled IOP who received prostaglandin analogs and a fixed-dose carbonic anhydrase inhibitor/beta-blocker combination were enrolled. All patients were additionally prescribed with brimonidine 0.2%. After a month, patients were divided into two groups based on achieved IOP level. In group 1, target IOP was achieved, and these patients were followed up. In group 2, target IOP was not achieved, and these patients underwent trabeculectomy. IOP was measured by elastotonometry and using the iCare tonometer. Results: a month after prescribing α2 agonist, true IOP level reduced to 14.0 (9.5; 17.0) mm Hg in group 1 and to 17.0 (13.0; 20.0) mm Hg in group 2. At the final visit, IOP levels were within target ranges in both groups, i.e., 13.0 (11.0; 18.5) mm Hg and 13.5 (9.7; 17.2) mm Hg, respectively. Meanwhile, changes in IOP measured by various methods were significantly different. IOP reduced by 5.4% (-7.1%; 17.6%) in group 1 and by 20.7% (4.4%; 30.7%) in group 2 (p<0.05) as measured by elastotonometry and by 8.3% (-11.8%; 28.6%) in group 1 and by 33.3% (13.9%; 50.7%) in group 2 as measured by iCare tonometer. Conclusions: brimonidine 0.2% provides additional IOP reduction to enhance maximum tolerated medical therapy for advanced POAG. An estimated effect of brimonidine is a 8% reduction of IOP from the baseline. If target IOP is not achieved, a patient should be scheduled for surgery. IOP should be measured using the iCare tonometer since this device is more sensitive to minor IOP fluctuations. Keywords: brimonidine 0.2%, maximum tolerated medical therapy for glaucoma, tonometry, elastotonometry, glaucoma, trabeculectomy, additive effect, target IOP. For citation: Dorofeev D.A., Balukhtina V.P., Es’kova M.V. et al. Additive effect of brimonidine in maximum tolerated medical therapy for primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2021;21(3):129–134 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-129-134.